2014
DOI: 10.1111/nmo.12408
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of in vivo colonic motor patterns in healthy humans before and after a meal revealed by high‐resolution fiber‐optic manometry

Abstract: Background Until recently, investigations of the normal patterns of motility of the healthy human colon have been limited by the resolution of in vivo recording techniques. Methods We have used a new, high-resolution fiber-optic manometry system (72 sensors at 1-cm intervals) to record motor activity from colon in 10 healthy human subjects. Key Results In the fasted colon, on the basis of rate and extent of propagation, four types of propagating motor pattern could be identified: (i) cyclic motor patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
338
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(366 citation statements)
references
References 70 publications
(159 reference statements)
18
338
3
Order By: Relevance
“…30 Similar studies in slow transit constipation patients have found a reduced daily frequency of high amplitude propagating sequences (also recognised as mass movements and responsible for a significant proportion of propulsive activity in the colon), and that all high amplitude propagating sequences originate in the proximal colon. 29,31,32 It is therefore plausible that the prolonged colonic transit times during oxycodone treatment in this study share-at least partly-pathophysiological characteristics with slow transit constipation, and that further development of the 3D-Transit software could elucidate this neglected, yet important aspect of GI motility. Along the same line, the increased transit in the rectosigmoid colon during oxycodone treatment could indicate that not only transit, but possibly also defecation, is affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Similar studies in slow transit constipation patients have found a reduced daily frequency of high amplitude propagating sequences (also recognised as mass movements and responsible for a significant proportion of propulsive activity in the colon), and that all high amplitude propagating sequences originate in the proximal colon. 29,31,32 It is therefore plausible that the prolonged colonic transit times during oxycodone treatment in this study share-at least partly-pathophysiological characteristics with slow transit constipation, and that further development of the 3D-Transit software could elucidate this neglected, yet important aspect of GI motility. Along the same line, the increased transit in the rectosigmoid colon during oxycodone treatment could indicate that not only transit, but possibly also defecation, is affected.…”
Section: Discussionmentioning
confidence: 99%
“…20 An alternative, but invasive, method to examine colonic motility patterns is high-resolution fiber-optic manometry. 29 A recent study employing this technique in slow transit constipation patients found that the normal increase in the postprandial propagating cyclic motor pattern was absent in patients when compared to healthy controls. 30 Similar studies in slow transit constipation patients have found a reduced daily frequency of high amplitude propagating sequences (also recognised as mass movements and responsible for a significant proportion of propulsive activity in the colon), and that all high amplitude propagating sequences originate in the proximal colon.…”
Section: Discussionmentioning
confidence: 99%
“…At one 1 cm spacing the retrograde motor patterns are by far the most prominent motor pattern identifi ed (Dinning et al , 2014. At one 1 cm spacing the retrograde motor patterns are by far the most prominent motor pattern identifi ed (Dinning et al , 2014.…”
Section: Future Directionmentioning
confidence: 96%
“…Quantifi cation of motor patterns recorded with these catheters in the healthy colon is only just beginning, however applying discriminant, logistic and cluster analysis of the shapes (gradient, duration, amplitude) of pressure events belonging to different motor patterns suggests that the motor appear to be generated by two independent sources, potentially indicating their neurogenic or myogenic origin (Dinning et al 2014 ). The clinical worth and the potential diagnostic value of such recordings in patient groups is still to be determined.…”
Section: Future Directionmentioning
confidence: 99%
“…A more recent development has been ’high resolution manometry’ (HRM) in which large numbers of pressure sensors are placed along the length of a catheter to record activity at ˜10 mm intervals along the gut . Optical fibre sensing arrays have been adapted for HRM recordings by a number of groups due to their inherent advantages of high flexibility, small dimensions, and the ability to multiplex many discrete sensing regions along a single fibre . HRM recordings reveal detailed intraluminal pressure profiles that have dramatically improved the ability of manometric studies to define both the normal and abnormal contractile patterns of the gut.…”
Section: Introductionmentioning
confidence: 99%